Mesures, développement : le statut de la créativité en question - Agathe Dirani
The specificities of creativity as a cross-sectorial skill have been analysed thanks to a survey in psychology, sociology and educational sciences dealing with measure, development and long-term effects of creativity. The main results seem to explain why this competence could not be incorporated by the French educational system. First of all, the uncertainty of long-term effects linked with creativity and the "adequationnist" logic that shaped the educational organisation kept it away from the main objectives of the French educational system. Secondly, the assessment model prevailing into the French educational system is not well equipped to furnish an appropriate measure of creativity., Thirdly, many specificities of the educational system, such as the weakness of interactions between schools and other social spaces enhancing the development of creativity limit its development.